The use of fusion images as a diagnostic and neurosurgical planning tool in microvascular decompression - Tommy, Thomas; Sakarunchai, Ittichai; Yamada, Yasuhiro; Yoshida, Koichiro; Kawase, Tsukasa; Kato, Yoko (Asian Journal of Neurosurgery, 2021)
Preoperative assessment of surgery using high-quality images can help surgeons to achieve best result of treatment. With the advances in computer technology, interactive multimodality fusion images have been developed. The use of fusion images as a preoperative planning tool is described with its examples in illustrative cases of trigeminal neuralgia and hemifacial spasm microvascular decompression (MVD). Interactive computer graphics such as multimodality fusion method is a useful tool to preoperatively predict the need of bone exposure and configuration of blood vessels with its correlation to cranial nerves in MVD.
Keywords: Fusion images; microvascular decompression; preoperative planning